Transgenerational crises of identity: growing up as colonial subjects in V. S. Naipaul's The Mimic Men and Luís Cardoso's The Crossing: a Story of East Timor - Martins, Adriana Alves de Paula (2011)
Despite belonging to distinct literary traditions, Luís Cardoso and V. S. Naipaul converge in their postcolonial reflection on what empires do to human beings in their books Crónica de uma Travessia and The Mimic Men. By focusing on the memories of two young islanders who grew up in colonies belonging respectively to the Portuguese and British empires, both writers address the crisis of identity faced by generations of colonial subjects as a result from imperial education and missionaries' work. This essay aims at examining how different imperial educational systems created and fed a sense of transtemporal alienated imagined identity, whose fragmented and artificial nature makes the colonized feel like exiles both in their own homelands and in the metropolis. By analysing the fathers' influence on Cardoso's and Naipaul's protagonists, the ideological and epistemological consequences of the lie underlying the civilizing mission will be highlighted and discussed.